1997
DOI: 10.1093/humrep/12.9.1993
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of growth of baboon primordial follicles in vitro

Abstract: Factors that cause some primordial follicles to enter the growth phase while the others remain quiescent are unknown. The hypothesis was tested that primate primordial follicles can survive and initiate growth in vitro in serum-free medium. Superficial pieces of ovarian cortex, containing mostly primordial follicles, were obtained from baboon fetuses during late gestation and cultured for 0, 2, 4, 7, 10 or 20 days in Waymouth MB 752/1 medium supplemented with insulin, transferrin, selenium, linoleic acid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
212
3
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(243 citation statements)
references
References 0 publications
24
212
3
4
Order By: Relevance
“…We found no major differences between androgenized and control ovaries when cortical tissue was cultured for up to 15 days. The proportion of growing follicles increased with time in culture in both types of ovary, a finding similar to our observations of cultured cortical biopsies from normal (Wright et al 1999) and polycystic human ovaries (Webber et al 2003) as well as reported studies in baboon (Wandji et al 1997) and cow (Wandji et al 1996). It was of interest that both progesterone and androstenedione were detected in conditioned medium from cultured biopsies of both types of ovary in these sheep studies (although there were no significant differences between the groups).…”
Section: Discussionsupporting
confidence: 91%
“…We found no major differences between androgenized and control ovaries when cortical tissue was cultured for up to 15 days. The proportion of growing follicles increased with time in culture in both types of ovary, a finding similar to our observations of cultured cortical biopsies from normal (Wright et al 1999) and polycystic human ovaries (Webber et al 2003) as well as reported studies in baboon (Wandji et al 1997) and cow (Wandji et al 1996). It was of interest that both progesterone and androstenedione were detected in conditioned medium from cultured biopsies of both types of ovary in these sheep studies (although there were no significant differences between the groups).…”
Section: Discussionsupporting
confidence: 91%
“…When cortical pieces were placed in culture, primordial follicles would be released from the influence of inhibitor(s) of medullary origin (Cushman et al, 2002), or the stimulatory factor(s) would override the effect of inhibitor(s) (Braw-Tal, 2002), allowing follicle activation to be initiated spontaneously even in the control medium (Wandji et al, 1996b;Braw-Tal and Yossefi, 1997). Other possible explanation for the spontaneous activation is that the fragmentation step, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few years the possible exploitation of preantral follicles from domestic animals, by isolation and culture, has received much attention , Jewgenow and Goritz, 1995, Nuttinck et al, 1996, Wandji et al, 1996, Lucci et al, 1999and Cecconi et al, 1999. However, in some studies, the results were not promising possibly due to follicle damage induced by the isolation procedures (Van den Hurk et al, 1997 and Katska and Rynska, 1998).…”
Section: Introductionmentioning
confidence: 99%